Engineering of Information Monitoring System Sensor Reading Data Based on Smart Wireless using NVDIA Jetson Nano and Arduino Mega on Agricultural Spraying Machines - Ridwan Siskandar; Tineke Mandang; Wawan Hermawan; Irzaman Irzaman (The University of Lampung, 2023)
The focus of the research is monitoring data from sensors on the agricultural sprayer. The monitoring system support by some sensors in camera, tank capacity, boom sprayer balance and battery capacity. The research method was carried out using the waterfall model, because according to the needs that require a sequential flow in the process. This model is divided into four parts, namely analysis (to identify problems and needs), design (plans to solve problems to be solved), implementation (implementation of plans that have been made), and testing. Engineering of Information Monitoring System Sensor Reading Data Based on Smart Wireless using NVDIA Jetson Nano and Arduino Uno on Agricultural Spraying Machines. The test results for the CNN model for the detection of the “Jajar Legowo” object were carried out to obtain 90% accuracy, 82.35% precision and 100% recall. Tests an accuracy value cappacity tank of 100%. Testing the balance sensor, if rotates clockwise on the Y axis the output voltage decreases, and vice versa. However, if the sensor at rest, the output voltage will same as the offset value. Besides that, testing the optimum PWM value fuzzy approach is carried out with aim that the droplets hit the target zone when sprayer is working. The result are Arduino IDE and Matlab produce same value, which is 42 for the optimum PWM value. Testing the battery capacity sensor get accuracy value of 100% by difference in the voltage increase of 0.5 volts is equivalent to increase of 10%. All information read by the sensors is displayed on the LCD using WMS-2000 (smart wireless). Keyword: Fuzzy, Microcontroller, Monitoring, Sensor data, Smart wireless